Clinical Management of an Outbreak of Visceral Schistosomosis in Sheep in Rewa, Madhya Pradesh - Chaurasiya, Rupesh; Dixit, Alok Kumar; Dixit, Pooja (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
Schistosomosis is an economically important disease of domestic animals and human being, mainly in the tropical and subtropical zones of the world. Schistosomosis is now recognized as the fifth major helminthosis of domestic animals in the Indian sub-continent. The disease has been reported in small ruminants by many workers (Cherian and D’Souza, 2009; Bhoyar et al., 2012). The species which commonly occur in India are Schistosoma nasale and S. spindale in cattle, S. indicum in horses and sheep and S. incognitum in pigs (D’Souza, 2006). S. indicum and S. spindale are the most prevalent causative agents of visceral schistosomosis. The disease is characterized by acute gastrointestinal symptoms in small ruminants where diarrhoea is the main clinical sign. Sometimes the disease is acute enough to cause death of the animal due to fluid and electrolyte losses or due to emboli formation by the parasite. The disease seems to be highly prevalent, but is under-diagnosed and has not received due attention.